Linking event quality to destination loyalty: a study on Coban to Coban Run Series in Malang - Finisya Dasmasela; Veny Megawati; Angeline Chrysanta Antolis (Faculty of Business and Economics, University of Surabaya, 2025)
Tourism is a sector that can boost Indonesia's foreign exchange. This is due to the availability of resources needed in developing tourism in the country, which resources are owned by Indonesia in the form of vast territory and the diversity that exists in the country. The potential of the destination area must have 3A in the form of attractive, amenities, accessibilities, facilities, with this, the government in the next five years is trying to increase tourism promotion by utilizing information technology strongly, and the government will develop culture-based tourism types and build a better tourism brand. This study aims to determine the effect of destination image, perceived value, tourist satisfaction, destination loyalty, and event quality on the Coban to Coban series event in Malang. The research conducted using causal research was tested quantitatively using SEM (Structural Equation Modeling), SPSS 18 software, and AMOS 22 software. The results of the study used 150 respondents and showed 6 significant positive supported hypotheses, and 1 hypothesis was not supported.